HISTORICAL FOLKLORE AND HISTORICAL REALITY (ABOUT LEGENDS AND PARABLES ABOUT HISTORICAL MONUMENTS IN USTYURT) - Kanaatov Esimkan Elsuyer uli (Western European Studies, 2024)
The article talks about the historical reality in legends and parables about the historical monuments of Ustyurt. The author conducts a historical and linguistic analysis of why historical places called Pulzhai, Tengeshashkan and Dzhezkempir received such a name. Readers are also offered interesting information about the sacred place in the southeastern part of Ustyurt – the mausoleum and cemetery of King Ibrahim Adham.
Keywords: Ustyurt; Pulzhai; historical reality; folklore